2015
DOI: 10.3389/fmicb.2015.00621
|View full text |Cite
|
Sign up to set email alerts
|

Zonation of bacterioplankton communities along aging upwelled water in the northern Benguela upwelling

Abstract: Upwelling areas are shaped by enhanced primary production in surface waters, accompanied by a well-investigated planktonic succession. Although bacteria play an important role in biogeochemical cycles of upwelling systems, little is known about bacterial community composition and its development during upwelling events. The aim of this study was to investigate the succession of bacterial assemblages in aging upwelled water of the Benguela upwelling from coastal to offshore sites. Water from the upper mixed lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…In fact, upwelling favorable winds cumulative intensity denoted an evident interannual upwelling variability during our study timeframe, characterized by a delayed and less intense events triggered during 2005-2006 ( Supplementary Figure 1). The influence of upwelling variability on nonphotosynthetic picoplankton has been reported in other seasonal upwelling ecosystems, such as, northwestern Indian Ocean (Wiebinga et al, 1997) and Benguela (Bergen et al, 2015) and agrees with previous results from the study area (Cuevas et al, 2004;Daneri et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, upwelling favorable winds cumulative intensity denoted an evident interannual upwelling variability during our study timeframe, characterized by a delayed and less intense events triggered during 2005-2006 ( Supplementary Figure 1). The influence of upwelling variability on nonphotosynthetic picoplankton has been reported in other seasonal upwelling ecosystems, such as, northwestern Indian Ocean (Wiebinga et al, 1997) and Benguela (Bergen et al, 2015) and agrees with previous results from the study area (Cuevas et al, 2004;Daneri et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Alonso-Gutiérrez et al (2009) revealed seasonal changes in the bacterioplankton community structure in the coastal upwelling region of "Ría de Vigo, " NW Spain, driven by Roseobacter, Bacteroidetes, and SAR86, as in this study. Bergen et al (2015) also revealed high abundances of Bacteroidetes and Gammaproteobacteria in productive upwelled waters in the Northern Benguela, in contrast to an abundance of Pelagibacterales in less productive waters, as also found in this study (i.e., Figures 4, 6).…”
Section: Nitrite and Ammonium Oxidationsupporting
confidence: 89%
“…These include Painting (1989) who also focused on the Southern Benguela, Kerkhof et al (1999) investigated the North Atlantic just off the New Jersey coast, Suzuki et al (2001) investigated an upwelling region in Monterey Bay in the NE Pacific and Teira et al (2009) studied six key bacterial groups in the Northwest Iberian Peninsula coastal upwelling waters. Only a handful of studies have included next generation sequencing techniques, which are capable of describing community diversity and structure in great detail (e.g., Bergen et al, 2015;Aldunate et al, 2018). These studies revealed a high occurrence of Bacteroidetes, Roseobacter, and SAR86 clade of gammaproteobacteria in upwelling waters.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence indicates that the non‐random distributions of microbial communities might follow a scale‐dependent distance‐decay relationship, and the increased spatial distance can usually limit the dispersal of microbes and contribute to accelerated speciation (Nemergut et al ., 2013; Liang et al ., 2015). Microbial biogeography is driven by ocean currents, water mass or up‐and down‐welling processes to create a distance‐decay pattern (Agogue et al ., 2011; Wilkins et al ., 2013; Bergen et al ., 2015); however, such a dispersal process was strongly context dependent and affected by depth, geographical range and perhaps season (Milici et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%